Brugada pattern in adolescent with acute myocarditis due to SARS‐CoV‐2 - David Bergamo; Courtney Nelson (Journal of the American College of Emergency Physicians Open)
Abstract Brugada syndrome is a genetic disorder characterized by abnormal findings on electrocardiogram (ECG) that can precipitate ventricular tachyarrhythmias and sudden cardiac death. Most clinical manifestations of Brugada syndrome are related to life‐threatening tachyarrhythmias, such as ventricular fibrillation or polymorphic ventricular tachycardia, but Brugada syndrome can also present with syncope or less likely palpitations. Our case is of a previously healthy 17‐year‐old visiting from Puerto Rico who presented to the emergency department (ED) with a syncopal episode preceded by sore throat, dizziness, and lightheadedness without palpitations. The ED evaluation found a normal complete blood count and basic metabolic panel. The patient tested positive for COVID‐19 by polymerase chain reaction. An ECG was performed that showed the Brugada pattern, which was later confirmed by cardiology. Although Brugada syndrome and pattern are well known to the medical population, the findings of Brugada pattern in the setting of COVID‐19 is not well described. Recognition and treatment are important, as Brugada syndrome can lead to life‐threatening arrhythmias and sudden cardiac death.